Checklist of the suborder Terebrantia (Thysanoptera): generic diversity and species composition in Xishuangbanna, Yunnan Province, China - Ntirenganya Elie (Pensoft Publishers, 2021)
Thysanoptera is amongst the most predominant orders of insects in different ecological zones with worldwide distribution. Due to their small size, there is a large gap in their distribution and host range data. To the best of our knowledge, there is no investigation on the thrips distribution and their host range in Xishuangbanna. Currently, a total of 566 species in 155 genera are listed in China, of which 313 species represent Terebrantia.In this study, a list of 116 species representing 55 genera within the families Aeolothripidae and Thripidae is provided. Two of these, Dichromomothrips nakahari Moud, 1976 (subfamily Thripinae) and Phibalothrips rugosus Kudo, 1979 (subfamily Panchaetothripinae) are recorded for the first time in China. Thrips species with their host ranges, habits and habitats are provided. Our study aims to contribute to the global biodiversity distribution data-gap of Thysanoptera for conservation purposes, as well as pest species targetting Integrated Pest Management tactics.